ByzRev 06.2024.047: Jesse W. Torgerson, The Chronographia of George the Synkellos and Theophanes.: The Ends of Time in Ninth-Century Constantinople (Brill’s Series on the Early Middle Ages 28). Leiden – Boston: Brill 2022. - Cecota, Błażej (The Byzantine Review, 2024)
Jesse W. Torgerson, The Chronographia of George the Synkellos and Theophanes. The Ends of Time in Ninth-Century Constantinople (Brill’s Series on the Early Middle Ages 28). Leiden – Boston: Brill 2022. xviii + 458 pp. – ISBN 978-90-04-50169-0